Field performance evaluation of geothermal ORC power plants with a focus on radial outflow turbines. (March 2020) - Zanellato, Luca; Astolfi, Marco; Serafino, Aldo; Rizzi, Dario; Macchi, Ennio
Abstract: The calculation of the performance of an ORC (Organic Rankine Cycle) and its components (in particularly the turbine) is generally not a trivial task because of the lack of a proper instrumentation, the inaccuracy of the available measurements and the uncertainty on fluid thermodynamic properties calculation. These limitations can greatly affect the final computed results especially for complex fluids with a small temperature drop in expansion. A strategy to solve the inconsistency of the measured data set is to verify the energy and mass balance of each component and of the overall plant using also information related to the geometry of specific components, primarily the turbine as well as electrical measurements. After a brief description of the radial outflow turbine and of its main features, two operating geothermal ORC (Organic Rankine Cycle) plants installed by Exergy Spa in Turkey are described. For both plants a methodology for the consistency check of the experimental data set is presented with a description of the installed instrumentation, the test procedure and methods used to calculate the turbine efficiency as well as the overall power cycle performance. Highlights: Experimental data of two geothermal ORC plants are sampled in steady state conditions. Advantages of radial outflow turbines compared to axial turbines are discussed. Two methodologies for the consistency check of the experimental dataset are proposed. ORC turbines efficiency are calculated with the corresponding uncertainty interval.